Evaluation of Phenological and Pomological Characteristics of Plum Varieties (Prunus spp. L.) in Mustang, Nepal - Kafle, Santosh; Atreya, Padma Nath; Timilsena, Ram Hari; Pokharel, Prayan; Khatri, Sushil; Adhikari, Biju; Bhandari, Niraj (Nepalese Horticulture, 2023)
Plum is a temperate stone fruit widely adapted and is by far the most diverse of all the 'Prunus' species. However, fruit and flower phenology and pomological characteristics differ among varieties. Phenological and pomological characteristics of six plum varieties ('Soldam,' 'Mirabelle,' 'Quetsche,' 'Methley,' 'Santa Rosa,' and 'Local') during September 2021-August 2022 in the fruit orchard of Temperate Horticulture Development Center, Mustang, Nepal, were studied. The phenological study revealed the Local as early and Quetsche as late among the tested varieties. However, the average flowering duration was lowest in Methley (10.6 days) and highest in Soldam (15.2 days). Linear dimensions of the fruits were maximum in Soldam and minimum in Mirabelle. The fruit shape of all the varieties was round except for Quetsche, which was elliptic. The stone share was highest in Mirabelle (7.82%) and lowest in Soldam (1.86%). The ripening index was highest for Mirabelle (29.11) and lowest for Methley (7.20). The organoleptic evaluation revealed that Soldam was the most preferred while Quetsche was the least. In conclusion, our study showcased a significant diversity in plum varieties, with implications for orchard management and variety selection to cater to various preferences and needs in the local market and beyond.